Interrogating cortical representations in elite athletes with persistent posterior thigh pain - New targets for intervention? - Summers, S. J.; Chalmers, K. J.; Wallwork, S. B.; Leake, H. B.; Moseley, G. L. (Journal of Science and Medicine in Sport, 2021)
Objectives: Hamstring injuries in athletes can lead to significant time away from competition as a result of persistent posterior thigh pain. These cases are often difficult to treat as the state of the tissues alone cannot explain symptoms. In non-athletic populations with persistent pain, disruptions to tactile, proprioceptive, and spatial cortical representations exist, which has led to promising brain-based treatments. Here, we explored whether athletes with persistent posterior thigh pain also display impairments in these cortical representations.